Pengaruh Penggunaan Media Sosial Tiktok Pada Anak Terhadap Efektivitas Komunikasi Kepada Orang Tua - Magna Syafrina; Silvina Mayasari; Sari Ekowati Hadi (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of TikTok social media usage on the effectiveness of communication between children aged 6–8 years and their parents. The background of this study is based on the widespread use of TikTok among children which can affect interaction patterns in the family, especially interpersonal communication between children and parents. This study uses a quantitative approach with a purposive sampling technique, involving 125 parents in Tlajung Udik Village, Gunung Putri District, Bogor Regency. Data were collected through questionnaires, then analyzed using validity tests, reliability, simple linear regression, classical assumption tests, and hypothesis tests (t-tests). The results showed that the significance value was 0.156> 0.05 and the t-count value was 1.429 <ttable 1.979. Thus, H₀ is accepted and Hₐ is rejected, which means that the use of TikTok does not have a significant effect on the effectiveness of communication between children and parents. However, a weak positive correlation was found (r = 0.128) and the coefficient of determination (R²) was only 1.6%. This means that the use of TikTok (X) does not affect the effectiveness of communication (Y).